Making Use of Shape Poem Technique in Project-based Learning for Teaching Writing - Mahayoni, Ni Putu Tia; Padmadewi, Ni Nyoman; Artini, Luh Putu (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
In English learning, students often struggle to understand the material, especially in mastering writing skills, one of the most difficult skills to be mastered. A well-chosen teaching technique and method will significantly impact students’ learning outcomes. The current study aimed to investigate the effect of the application of the shape poem technique combined with the project-based learning on students’ writing skills. This study employs a quantitative research approach using a pre-experimental design, one group pre-test post-test. This study involved 38 students of at SMPN 1 Singaraja as a sample. To conduct the study, tests were given before and after the treatment. The findings demonstrated that implementation of the shape poem technique led to substantial enhancements in students' writing skills, as evident from the pre-test and post-test scores. The test result shown that students’ gain better outcomes in post-test which after the treatment was given. It is also supported by the t-test result that shown the significant level was below the alpha level (α = 0.05), indicated the alternative hypothesis was accepted, that there is a significant effect on 7th grade students’ writing skills. The combination of shape poem technique and project-based learning might provide a fresh viewpoint for teachers in teaching writing.